Health psychology a textbook - Ogden, Jane 1966- (Open University Press, 2004)
This third edition has now been extensively updated and considerably strengthened in a number of key areas...it provides a clear, comprehensive and up-to-date overview of a wide range of research and theory...it clearly deserves to maintain its place as the number one choice of health psychology textbook." - John Weinman, King's College, London. Praise for the previous edition include: "The volume of work undertaken by Ogden for the first edition of her textbook was impressive, and the second edition is even better...As a text aimed at undergraduate psychology students, it is hard to fault." - "Times Higher Education Supplement" ("The Textbook Guide")."Health Psychology: A Textbook" has made a major contribution to the teaching and study of this rapidly expanding discipline. Maintaining its strong review of theory and research and its details of behaviours such as smoking, exercise, eating and screening, the third edition has been substantially revised to provide increased coverage of the biological aspects of health and illness.This book now provides the most accessible and comprehensive guide to the field. Many new features have been incorporated into this edition to further aid students and teachers, including: additional, entirely new chapter on stress; now two chapters address this key topic; expanded and improved section on psychoneuroimmunology (PNI); expanded chapter on pain; new section on the consequences of coronary heart disease (CHD) and rehabilitation of CHD patients; new chapter on eating behaviour; and new coverage of problems associated with social cognition models.The new two-colour layout has been designed with students in mind, including clear illustrations, boxed discussion points, and specific research boxes. New to this edition are: Online Learning Centre (OLC) with great materials for students and lecturers. The resources include further readings, "Focus on Research" boxes, web links, sample essay questions, chapter overviews, PowerPoint slides and an instructor resource manual. The OLC content enhances the learning experience for students and provides support for lecturers teaching the subject. "Health Psychology: A Textbook" is essential reading for all students and researchers of health psychology and for students of medicine, nursing and allied health courses.